Service Oriented Mobile Wallets with NFC - Mehmet Ali Erturk; M. Ali Aydin; H. Ibrahim Ibali; Zeynep Gurkas Aydin; A. Halim Zaim (International Journal of Applied Methods in Electronics and Computers, 2016)
Near Field Communication (NFC) technology integration with mobile phones has extended the way we use mobile devices. Instead of voice and text communication mobile devices can be used as credit cards to replace our wallets. In this study we have developed an NFC based mobile wallet with using Alcatel Lucent Mobile Wallet web services with provided functionalities such as accounts, e-money, loyalty cards, etc. These services are consumed from NFC mobile phones and NFC device is used for payments and secure store to keep user credentials in SIM Secure Element.